(untitled) (Research, Society and Development, 2024)
Introduction: Adult acne (AMA) is a growing concern due to its impact on self-esteem and skin aesthetics. This study investigated the effectiveness of spironolactone in the treatment of AMA. The present article aims to provide a comprehensive update of available treatments for acne, focusing on an emerging and promising therapeutic agent: spironolactone. Methodology: Terms such as "Acne and Spironolactone", "Woman and acne" and "Spironolactone and acne treatment" were used. Ten articles were selected, including clinical and observational studies of works published between 2017 and 2023, searched in the SciELO, PubMed, Google Scholar and VHL databases. Results and discussion: Spironolactone, initially indicated for other conditions, has promising effects in AMA due to its potential androgenic antagonism. Spironolactone is often used in combination with other treatments, and despite side effects, its tolerance is generally good. The average dosage used was 100 mg for six months, adjusted according to adverse effects. Multicenter studies have indicated a low risk of hyperkalemia with the use of spironolactone to treat AMA. Research has also highlighted spironolactone’s ability to treat injuries in several areas, including the face and trunk. Conclusion: Spironolactone emerges as a promising therapeutic option for adult acne, despite limited scientific evidence. Its use has demonstrated effectiveness in controlling lesions, especially when associated with topical retinoids. It is crucial to monitor kidney function and potassium levels. Additional studies are needed to consolidate its role in the treatment of AMA and fully understand its effectiveness and safety.